IMPLEMENTATION OF 12 CORE COMPETENCY TRAINING, PRECEPTORSHIP METHOD FOR NEW NURSES IN IMPROVING THE 12 CORE COMPETENCIES OF NEW NURSES AT PRIMAYA PGI CIKINI HOSPITAL, CENTRAL JAKARTA - Tarigan, Juliani; Tutupoly, Johana (Holistic Nursing Plus, 2026)
In accordance with the Hospital Law No. 44 of 2009 concerning hospitals, hospitals must have nursing staff including New Nurses. New nurses in their work environment are found to lack clinical, social and emotional support which reduces their confidence in practicing nursing care such as lack of knowledge and practical competence when facing complex situations in the work environment. According to SKPI 2012, nurses must be able to carry out 12 basic nursing competencies competently. The implementation of 12 core competencies for new nurses is very important to improve nurse competence. The purpose of this study is to determine the effectiveness of training on the implementation of 12 core competencies by Preceptors on improving 12 core competencies for New Nurses. The research method uses quantitative research with a quasi-experimental design with a pretest-posttest control group design, namely a two-group design selected by consecutive sampling that meets the inclusion criteria with a sample of 20 new nurses, 10 nurses in the intervention group and 10 nurses in the control group. The results of the normality and homogeneity tests showed that the data were normally distributed and both groups had homogeneous variances, so the selection of parametric statistical tests such as the paired t-test and independent t-test was appropriate. The results of the paired t-test in the intervention group showed a significant difference between the pre-test and post-test scores. The calculated t-value of 9.487 was greater than the t-table, and the significance value of 0.001 was less than 0.05, indicating that the training in implementing the 12 core competencies had a significant impact on improving the competency of new nurses. Conclusion: The implementation of the 12 core competencies improved technical nursing skills, professional competencies, teamwork, responsibility, and clinical decision-making abilities, which are the core of professional nursing practice.